PERAN KOMITE ANTI DUMPING INDONESIA (KADI) MENANGANI PRAKTIK DUMPING PERDAGANGAN CHINA-INDONESIA (Studi Kasus Polyester Staple Fiber dari China Tahun 2009 – 2010) - Agita Tarigan; Tri Cahyo Utomo; Wiwik Widayati (Journal of Politic and Government Studies, 2013)
Polyester Staple Fiber is a material that is produced from synthetic chemical and compound with various uses in industry phrase. There are states that export material of Polyester Staple Fiber to Indonesia like China, Taiwan, Thailand, South Korea, Malaysia and India. Among those states, dumping practices was found in Indonesian international trade which is implementing by the exporters. Dumping occur when a foreign company sells a product to the another state at less than fairmarket value. Loss caused to states who imports goods which contain dumping, therefor dumping is prohibited in international trade which have been mentioned by World Trade Organization (WTO).Dumping was done by China in the exporting activity of Polyester Staple Fiber. The lower price that is provided of China’s Polyester Staple Fiber is the reason that makes the Indonesian consumer interested of buying it more than the inland production. That thing decrease the market share of the inland producers company and caused loss. To anticipate the increasing of loss, Indonesian Fiber Synthetic Producer Association (APSYFI) made a petition to the Indonesian Antidumping Committee.The petition of Indonesian Fiber Synthetic Producer Association (APSYFI) that was represented by two national Polyester Staple Fiber company which are PT. Teijin Indonesia Fiber Corporation (Tifico) and PT Indonesia Toray Synthetic (Toray) continue to an investigation in proving dumping containing of the China’s Polyester Staple Fiber export. The end of the investigation, Indonesian Antidumping Committee recommended the antidumping duties of China’s Polyester Staple Fiber export to the Minister of Commerce and Minister of Finance. This duties purposed to protect inland producers from the continue of loss that caused by dumping.Keywords: Dumping, Polyester Staple Fiber, The Indonesian Antidumping Committee